2013
DOI: 10.1124/mol.113.085795
|View full text |Cite
|
Sign up to set email alerts
|

An Unusual Pattern of Ligand-Receptor Interactions for theα7 Nicotinic Acetylcholine Receptor, with Implications for the Binding of Varenicline

Abstract: The a7 nicotinic acetylcholine receptor shows broad pharmacology, complicating the development of subtype-specific nicotinic receptor agonists. Here we use unnatural amino acid mutagenesis to characterize binding to a7 by the smoking cessation drug varenicline (Chantix; Pfizer, Groton, CT), an a4b2-targeted agonist that shows full efficacy and modest potency at the a7 receptor. We find that unlike binding to its target receptor, varenicline does not form a cation-p interaction with TrpB, further supporting a u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
31
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(39 citation statements)
references
References 41 publications
6
31
2
Order By: Relevance
“…Other studies have shown that acetylcholinesterase inhibitors effectively modulate the acute colonic inflammation in colitis possibly by an increase in the cholinergic tone of the colon (Miceli and Jacobson, 2003). Vagal nerve stimulation via ACh also ameliorates disease activity (van der Zanden et al, 2009). In this same study, it has been shown that vagotomized a7 nAChR knockout mice display more severe colitis than wild-type mice.…”
Section: G A7 Nicotinic Acetylcholine Receptors and The Immune Connesupporting
confidence: 55%
See 1 more Smart Citation
“…Other studies have shown that acetylcholinesterase inhibitors effectively modulate the acute colonic inflammation in colitis possibly by an increase in the cholinergic tone of the colon (Miceli and Jacobson, 2003). Vagal nerve stimulation via ACh also ameliorates disease activity (van der Zanden et al, 2009). In this same study, it has been shown that vagotomized a7 nAChR knockout mice display more severe colitis than wild-type mice.…”
Section: G A7 Nicotinic Acetylcholine Receptors and The Immune Connesupporting
confidence: 55%
“…Computer modeling further pointed to the role of fractional hydrophobicity/ hydrophilicity of the LBD and the contribution of the cation-p interaction of the ligand's basic nitrogen atom with tryptophan 149 of the LBD (Kombo and Bencherif, 2013). The LBD interaction with a ligand is, however, probably more complex, as revealed by studies conducted using nonnatural amino acids that point to an unusual interaction of varenicline with a7 nAChRs and the absence of a cation-p interaction with a tryptophan residue (Van Arnam et al, 2013). This study further revealed that the leucine at position 119 and tryptophan at position 55 are important for the binding of large molecules such as epibatidine or varenicline but are dispensable for binding of smaller molecules such as ACh.…”
Section: B Functional Properties Of A7 Nicotinic Acetylcholine Recepmentioning
confidence: 99%
“…Alzheimer's disease, epilepsy, neurodegeneration and cognitive deficits in Parkinson's disease, and schizophrenia (Changeux and Edelstein, 2005;Zhang et al, 2012;van Arnam and Dougherty, 2014). Normally, it has yielded the viewpoint that neuronal nAChRs exercise a principally regulative effect in the CNS, and this notion has been ratified by several biological proofs (van Arnam et al, 2013;Schaaf, 2014). As consequence, neuronal nAChRs have attracted increasingly attention of multidisciplinary scientists and further become the vital target receptors for the developments of various pharmaceuticals (Fraenkel et al, 1996;Petersen et al, 2015).…”
Section: Introductionmentioning
confidence: 98%
“…We also applied a previously described strategy for evaluating the two key H-bonding interactions at the agonist binding site (Tavares, et al, 2012; Van Arnam, et al, 2013). Briefly, α-hydroxy analogues of α-amino acids are incorporated in ways that are known to strongly modulate the hydrogen bonding ability of the protein backbone (Figure S1).…”
Section: Resultsmentioning
confidence: 99%
“…Non-canonical amino acid mutagenesis provides high-resolution data that complement those from X-ray crystallography. The key binding interactions at the agonist binding site of nAChRs – a cation-π interaction and two hydrogen bonds – can be probed in ways that would be sensitive to ligand displacements of <1 Å (Dougherty and Van Arnam, 2014; Tavares, et al, 2012; Van Arnam, et al, 2013). We have therefore applied non-canonical amino acid mutagenesis to ask whether the presence of a PAM in any way modulates these binding interactions at the orthosteric site.…”
Section: Introductionmentioning
confidence: 99%